2014
DOI: 10.1159/000363540
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Guideline Reduces the Need for Red Blood Cell Transfusions in Swiss Hospitals: A Prospective, Multicentre, Before-and-After Study in Elective Hip and Knee Replacement

Abstract: Introduction: Optimising the use of blood has become a core task of transfusion medicine. Because no general guidelines are available in Switzerland, we analysed the effects of the introduction of a guideline on red blood cell (RBC) transfusion for elective orthopaedic surgery. Methods: Prospective, multicentre, before-and-after study comparing the use of RBCs in adult elective hip or knee replacement before and after the implementation of a guideline in 10 Swiss hospitals, developed together with all particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Politsmakher et al showed that the implementation of a hospital monitoring program reduced the rate of RBC transfusion by 38.1% in his study setting, which was associated with a decrease in morbidity and mortality [ 41 , 42 ]. Similar to our study but in the intensive care setting Hebert et al conducted a survey among physicians using case scenarios which showed, that 85% of physicians had modified their approach to transfusion, primarily in response to the publication of a major Canadian clinical trial and institutional guidelines [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Politsmakher et al showed that the implementation of a hospital monitoring program reduced the rate of RBC transfusion by 38.1% in his study setting, which was associated with a decrease in morbidity and mortality [ 41 , 42 ]. Similar to our study but in the intensive care setting Hebert et al conducted a survey among physicians using case scenarios which showed, that 85% of physicians had modified their approach to transfusion, primarily in response to the publication of a major Canadian clinical trial and institutional guidelines [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…50% of the physicians reported the absence of local transfusion guidelines for RBC administration. At present, no Swiss national guidelines exist regarding RBC transfusion practice in patients without acute blood loss [ 42 ]. The majority of the interviewed physicians (84%) would support the development of national treatment recommendations on transfusion of RBC in non-acutely bleeding patients with anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Any delay in diagnosis will obviously also delay the start of treatment and subsequently the recovery of a patient with PTO, hence overall costs will increase. It is known from other orthopaedic studies that, as a general rule, both patients and cost effectiveness benefit from clinical pathways and guidelines [ 30 , 31 ]. There is thus a need for a lean and strict algorithm on diagnosing PTO.…”
Section: Discussionmentioning
confidence: 99%
“…Given such remaining uncertainty it seems reasonable to consider additional risk factors beside a Hb cut-off as criteria for RBC transfusion as proposed by Fontana and coworkers in a recent prospective interventional study in orthopedic patients [41]. Similarly Theusinger and coworkers propose to decide on RBC, FFP and platelet transfusion on a case-per-case basis rather than on a specific medical laboratory profile issued as transfusion trigger [42], an approach bearing biologic variation in mind.…”
Section: Critical Appraisal Of Transfusion Trigger Cutoffs Set By Larmentioning
confidence: 99%